Fine Sediment Dispersion in the Addu-City Dredging and Reclamation Project - Efstratios N. Fonias; Erik van Eekelen; Barend van den Bosch (Journal of Marine Science and Engineering)
The matter of the quantification of the fraction of the dredged sediment that is released by a trailing suction hopper dredger into the surrounding waters, also known as the passive phase of the plume during dredging operations through the overflow, is a rather complex process. A number of processes, including sediment settling, propeller wash, and entrapment of air during sediment release, are only a few of the reasons why plumes are formed and sediments because of the overflow are released back into the environment. The present work attempts to examine the empirical considerations used for the estimation of the amount of sediments expected to be released through the overflow or via a reclamation by looking into the case of the Addu-City dredging and reclamation project. Moreover, the effectiveness of silt curtains as a turbidity containment measure is discussed. Based on the field data collected, it can be concluded that under normal hydrodynamic conditions, from the sediment source calculated based on the existing literature, only 20% of the fine sediments is available for dispersion. Moreover, the accurate and consistent follow-up of the work schedule execution and consistent monitoring as a part of environmental management can ensure compliance with environmental regulations further away from the project area.